Low-Dose Heparin Protocol in Type A Aortic Dissection Surgeries - Mavioglu, Levent; Karahan, Mehmet; Unal, Ertekin Utku; Celikten, Ayla Ece; Demir, Asli; Iscan, Hakki Zafer; Ozatik, Mehmet Ali (The Thoracic and Cardiovascular Surgeon, 2022)
Objective We aim to compare the heparin dose regimen in terms of bleeding, reoperation rate due to severe bleeding, and the amount of transfusion of the blood products in patients who underwent surgery for type A aortic dissection (TAAD).Materials and Methods Between January 2018 and August 2021, 90 adult patients who underwent for TAAD were included. Primary outcome measures were postoperative bleeding amount and blood product transfusion requirements. Two different protocols performed in TAAD surgery in our clinic. In this pre- and postimplementation study, before October 2019, the standard-dose heparin protocol (SH group) was used and after November 2019, the low-dose heparin protocol (LH group) was used and two groups were compared. Mechanical ventilation duration, length of intensive care unit and hospital stay, postoperative drainage volumes, blood product transfusions, reoperations due to bleeding, and in-hospital mortality rates were recorded.Results The dosages of heparin and activated clotting time values, as well as the additional heparin requirement, were significantly different between the two groups (p < 0.001). Standard-dose heparinization was needed only in 33.3% of patients in the LH group. In the SH group, postoperative total drainage and red blood cell (RBC) transfusion were significantly higher than the LH group (p = 0.036 and p = 0.046, respectively).Conclusion We found that the low-dose heparin regimen resulted in significantly less postoperative total drainage and RBC transfusion requirement in patients who underwent for TAAD.
Keywords: aortic dissection; heparin; red blood cell transfusion